Green synthesis of ZnO nanoparticles and their photocatalyst degradation and antibacterial activity - D Kamarajan; Benny Anburaj; V Porkalai; A Muthuvel; G Nedunchezhian; N Mahendran (Journal of Water and Environmental Nanotechnology, 2022)
The current study aimed to synthesize nanoparticles of Zinc oxide (ZnO) using the extract of Acalypha indica leaves and their photocatalyst degradation and antibacterial properties were also measured. The biosynthesized nanoparticles were analyzed using XRD, UV-visible, FT-IR, and SEM with EDAX, DLS, PL, and Zeta potential analysis. The synthesized nanoparticles had a mean size of 16 nm measured by XRD which was highly pure, and their spherical shape was confirmed by SEM. The UV-visible confirmed that ZnO nanoparticles have a direct band gap energy is 3.34 eV. The measured zeta size and potential of synthesized nanoparticles were 46 nm and -27 mV, respectively, determined by the DLS technique can be considered moderately stable colloidal solutions. The FT-IR analysis confirmed the presence of functional groups in the leaf extract and the ZnO nanoparticles. The biosynthesized ZnO nanoparticles have a homogeneous spherical morphology and the average particle is 35 nm. The PL analyses performed on synthesized nanoparticles showed a sharp blue band at 362 nm, which was attributed to the defects of structure in ZnO crystals. During natural sunlight illumination, ZnO nanoparticles demonstrated notable degradation of the dye methyl blue (MB). At 90 min of illumination, the degradation efficiency achieved was 96 %. Antibacterial properties were observed for synthesized nanoparticles against four bacterial strains, including Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. The highest zone of inhibition was observed against Escherichia coli (25.2 mm). Overall, these studies indicate that Acalypha indica is a good sell for planting, and has the greatest chance of being used to develop nanoparticles for protection against environmental pollution and human health.